A Scalable RISC-V Hardware Platform for Intelligent Sensor Processing - Palomero Bernardo, Paul; Schmid, Patrick; Bringmann, Oliver; Iftekhar, Mohammed; Sadiye, Babak; Müller, Wolfgang; Koch, Andreas; Jentsch, Eyck; Sauer, Axel; Feldner, Ingo; Ecker, Wolfgang (DATE 24 - Design Automation and Test in Europe)

Team-Teaching und Kompetenzen von Kindern im inklusiven naturwissenschaftlichen Sachunterricht. Vortrag auf der Tagung der Österreichischen Gesellschaft für Forschung und Entwicklung im Bildungswesen (ÖFEB). Thema: „Diversität diskursiv. Bildungswissenschaftliche Zugänge und pädagogische Perspektiven". - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Effekte eines universitären Kooperationstrainings auf inklusionsbezogene Selbstkonzepte von Lehramtsstudierenden. Vortrag auf der Tagung der Österreichischen Gesellschaft für Forschung und Entwicklung im Bildungswesen (ÖFEB). Thema: „Diversität diskursiv. Bildungswissenschaftliche Zugänge und pädagogische Perspektiven". - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Effekte eines universitären Lehrerkooperationstrainings auf die inklusionsbezogenen Selbstkonzepte angehender Lehrkräfte. Vortrag auf der 11. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung verstehen – Partizipation erreichen – Transfer gestalten“. - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Effects of a collaborative teacher education on pre-service teachers’ inclusion-related self-concept. Oral Paper Presentation. EARLI SIG 15 Biennial Conference 2024 ‘Special Educational Needs’. “Neurodiversity in Education: Research and Practice”. - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Effects of University Teacher Collaboration Training on the Inclusion-Related Self-Concepts of Prospective Teachers. - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

„Wir wollen mitreden!“ – Entwicklung und Validierung von Skalen zur Erfassung motivationaler Regulation bei der Teilnahme an Befragungen zur Evaluation des Studiums (SMR-Eval) - Koppenborg, Markus; Klingsieck, Katrin B. (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung: Für die Evaluation und Qualitätsentwicklung von Studium und Lehre werden häufig quantitative Befragungen von Studenten eingesetzt. Jedoch ist häufig unklar, aus welcher Motivation Studenten an den Befragungen teilnehmen und inwieweit unterschiedliche motivationale Regulationsstile mit dem Antwortverhalten im Fragebogen zusammenhängen. Ausgehend von der Selbstbestimmungstheorie der Motivation nach Deci und Ryan stellt der Beitrag die Entwicklung der Skalen zur motivationalen Regulation bei Befragungen zur Evaluation (SMR-Eval) vor. Studie 1 zeigt die fünffaktorielle Struktur des Instruments. Studie 2 weist auf eine starke Messinvarianz bezüglich Geschlecht, Abschlussziel und Fakultät hin. Korrelationen mit Drittvariablen belegen die konvergente Validität der fünf Subskalen. In Studie 3 werden latente Profilanalysen über die fünf Regulationsstile berechnet. Die Ergebnisse zeigen vier Profile, welche sich inhaltlich plausibel im Antwortverhalten der Befragten unterscheiden und damit Hinweise auf die Kriteriumsvalidität der Skalen geben. Diskutiert werden theoretische und praktische Implikationen für Evaluationsvorhaben an Hochschulen sowie Übertragungsmöglichkeiten auf andere Evaluationsgegenstände.
Keywords: Developmental and Educational Psychology

Can leaders motivate employees’ energy-efficient behavior with thoughtful communication? - Hoffmann, Christin; Thommes, Kirsten (Journal of Environmental Economics and Management)
Keywords: Management; Monitoring; Policy and Law; Economics and Econometrics

Komplexität von Verrechnungspreisen und Tax Compliance: Einblicke in deutsche Unternehmen - Greil, Stefan; Kaluza-Thiesen, Eleonore; Schulz, Kim Alina; Sureth-Sloane, Caren (Deutsches Steuerrecht)

Cold denaturation of DNA origami nanostructures - Dornbusch, Daniel; Hanke, Marcel; Tomm, Emilia; Kielar, Charlotte; Grundmeier, Guido; Keller, Adrian; Fahmy, Karim (Chemical Communications)
The coupling of structural transitions to heat capacity changes leads to destabilization of macromolecules at both, elevated and lowered temperatures. DNA origami not only exhibit this property but also provide...
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

“Look me in the eye, customer”: How do face-to-face interactions in peer-to-peer sharing economy services affect customers’ misbehavior concealment intentions? - Ozuna, Edna; Steinhoff, Lena (Journal of Business Research)
Customer misbehavior poses a major risk in the sharing economy. For example, property damage to shared accommodations imposes burdens on both sharing platforms and hosts, especially if misbehaving guests purposefully, not coincidentally conceal, or fail to report damages. Such misbehavior might be facilitated by remote listing management and the lack of face-to-face interactions between hosts and guests. Therefore, this study investigated the effects of host–guest interaction modes (face-to-face, online-only) and frequency on guests’ misbehavior concealment intentions. Social identification and irritation emerged as bright- and dark side mediators, respectively. Guests who interacted face-to-face (vs. online-only) with hosts exhibited weaker intentions to conceal their misbehavior due to increased social identification. Platforms can elicit social identification by engaging guests in virtual communities. However, when face-to-face interactions become excessive, guests experience irritation and are more likely to conceal their misbehavior. These insights offer practical implications for both peer-to-peer sharing platforms and hosts.
Keywords: Sharing economy; Customer misbehavior; Peer-to-peer services; Face-to-face interactions; Experimental research

Playing games with QCA: Measuring the explanatory power of single conditions with the Banzhaf index - Haake, Claus-Jochen; Schneider, Martin (Journal of International Management)
Qualitative comparative analysis (QCA) enables researchers in international management to better understand how the impact of a single explanatory factor depends on the context of other factors. But the analytical toolbox of QCA does not include a parameter for the explanatory power of a single explanatory factor or “condition”. In this paper, we therefore reinterpret the Banzhaf power index, originally developed in cooperative game theory, to establish a goodness-of-fit parameter in QCA. The relative Banzhaf index we suggest measures the explanatory power of one condition averaged across all sufficient combinations of conditions. The paper argues that the index is especially informative in three situations that are all salient in international management and call for a context-sensitive analysis of single conditions, namely substantial limited diversity in the data, the emergence of strong INUS conditions in the analysis, and theorizing with contingency factors. The paper derives the properties of the relative Banzhaf index in QCA, demonstrates how the index can be computed easily from a rudimentary truth table, and explores its insights by revisiting selected papers in international management that apply fuzzy-set QCA. It finally suggests a three-step procedure for utilizing the relative Banzhaf index when the causal structure involves both contingency effects and configurational causation.
Keywords: Qualitative comparative analysis; Banzhaf power index; causality; explanatory power

The association between dairy intake in adolescents with inflammation and risk markers of type 2 diabetes during young adulthood – results of the DONALD study - Hohoff, E; Jankovic, N; Perrar, I; Schnermann, ME; Herder, C; Nöthlings, U; Libuda, Lars; Alexy, U (Public Health Nutrition)
ABSTRACT OBJECTIVE: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, not-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. DESIGN: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on hsCRP, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as HOMA2-IR in an open cohort study. SETTING: Dortmund, Germany PARTICIPANTS: Data from participants (n=375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-day weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. RESULTS: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all p>0.05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all p>0.05). CONCLUSIONS: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Reflexion im Dialog. Ein Modell für eine Kinder, Eltern, Teams und Schule stärkende Bildungsdokumentation. - Büker, Petra; Höke, Julia (Grundschule aktuell)

Kinderstärkende Pädagogik in der Schule im Kontext aktueller Herausforderungen. Kennzeichen, Anfragen und mögliche Blinde Flecke. Keynote an der Tagung: Die Kunst der Partizipation. PH Zürich. - Büker, Petra

Optical Bias and Cryogenic Laser Readout of a Multipixel Superconducting Nanowire Single Photon Detector - Thiele, Frederik; Lamberty, Niklas; Hummel, Thomas; Bartley, Tim (arXiv:2403.14276)
Cryogenic opto-electronic interconnects are gaining increasing interest as a means to control and read out cryogenic electronic components. The challenge is to achieve sufficient signal integrity with low heat load processing. In this context, we demonstrate the opto-electronic bias and readout of a commercial four-pixel superconducting nanowire single-photon detector array using a cryogenic photodiode and laser. We show that this approach has a similar system detection efficiency to a conventional bias. Furthermore, multi-pixel detection events are faithfully converted between the optical and electrical domain, which allows reliable extraction of amplitude multiplexed photon statistics. Our device has a passive heat dissipation of 2.6mW, maintains the signal rise time of 3ns, and operates in free-running (self-resetting) mode at a repetition rate of 600kHz. This demonstrates the potential of high-bandwidth, low noise, and low heat load opto-electronic interconnects for scalable cryogenic signal processing and transmission.

Noctua 2 Supercomputer - Bauer, Carsten; Kenter, Tobias; Lass, Michael; Mazur, Lukas; Meyer, Marius; Nitsche, Holger; Riebler, Heinrich; Schade, Robert; Schwarz, Michael; Winnwa, Nils; Wiens, Alex; Wu, Xin; et al. (Journal of large-scale research facilities)
Noctua 2 is a supercomputer operated at the Paderborn Center for Parallel Computing (PC2) at Paderborn University in Germany. Noctua 2 was inaugurated in 2022 and is an Atos BullSequana XH2000 system. It consists mainly of three node types: 1) CPU Compute nodes with AMD EPYC processors in different main memory configurations, 2) GPU nodes with NVIDIA A100 GPUs, and 3) FPGA nodes with Xilinx Alveo U280 and Intel Stratix 10 FPGA cards. While CPUs and GPUs are known off-the-shelf components in HPC systems, the operation of a large number of FPGA cards from different vendors and a dedicated FPGA-to-FPGA network are unique characteristics of Noctua 2. This paper describes in detail the overall setup of Noctua 2 and gives insights into the operation of the cluster from a hardware, software and facility perspective.
Keywords: Noctua 2; Supercomputer; FPGA; PC2; Paderborn Center for Parallel Computing

Ich darf auch „Nein“ sagen: Das Kinderrecht auf informierte Einwilligung und dessen Implikationen. Beitrag im Rahmen des Symposiums „Partizipation an, mit und über Forschung? Dilemmata und forschungsethische Reflexionen im Prozess des Forschens mit Kindern. Symposium an der Tagung: Die Kunst der Partizipation. PH Zürich. - Büker, Petra; Deckert-Peaceman, Heike; Hüpping, Birgit; Zala-Mezö, Enikö

Visual Tracking Nonlinear Model Predictive Control Method for Autonomous Wind Turbine Inspection - Amer, Abdelhakim; Mehndiratta, Mohit; le Fevre Sejersen, Jonas; Pham, Huy Xuan; Kayacan, Erdal (2023 21st International Conference on Advanced Robotics (ICAR))

Predicting PDEs Fast and Efficiently with Equivariant Extreme Learning Machines - Harder, Hans; Peitz, Sebastian
We utilize extreme learning machines for the prediction of partial differential equations (PDEs). Our method splits the state space into multiple windows that are predicted individually using a single model. Despite requiring only few data points (in some cases, our method can learn from a single full-state snapshot), it still achieves high accuracy and can predict the flow of PDEs over long time horizons. Moreover, we show how additional symmetries can be exploited to increase sample efficiency and to enforce equivariance.
Keywords: extreme learning machines; partial differential equations; data-driven prediction; high-dimensional systems